2022
DOI: 10.3390/jcdd9030068
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Assessment of Atrial Function: From Basic Mechanics to Specific Cardiac Diseases

Abstract: The left and right atria serve as buffer chambers to control the flow of venous blood for ventricular filling. If an atrium is absent, blood does not flow effectively into the ventricle, leading to venous blood retention and low cardiac output. The importance of atrial function has become increasingly recognized, because left atrial (LA) function contributes to cardiac performance, and loss of LA function is associated with heart failure. LA volume change has been used for LA function assessment in experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 100 publications
(116 reference statements)
1
4
0
Order By: Relevance
“…Most studies of LA MD have defined the parameter as SD-TPS corrected by the R-R interval (%) instead of the crude SD-TPS value in ms. 14,17,28,30 Endurance athletes experience exercise-induced bradycardia and as expected, the athletes in the present study had a lower resting heart rate than the non-athletic group. 31 Hence, we introduced an association between athletic status and LA MD when correcting SD-TPS by the R-R interval.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Most studies of LA MD have defined the parameter as SD-TPS corrected by the R-R interval (%) instead of the crude SD-TPS value in ms. 14,17,28,30 Endurance athletes experience exercise-induced bradycardia and as expected, the athletes in the present study had a lower resting heart rate than the non-athletic group. 31 Hence, we introduced an association between athletic status and LA MD when correcting SD-TPS by the R-R interval.…”
Section: Discussionsupporting
confidence: 84%
“…It is reported to be a novel predictor of AF in the general population, linked to the recurrence of AF after catheter ablation, and associated with stroke among AF patients. [14][15][16][17] Watanabe et al found an association between increased LA MD and low voltage zones recognized by voltage mapping in paroxysmal AF patients indicating regional fibrosis in the LA wall. 18 There has also been a report of increased atrial fibrosis assessed by magnetic resonance imaging (MRI) in a group of healthy veteran endurance athletes, linking long-term endurance exercise to increased atrial fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cardiac Amyloidosis, the left atrium is impaired like the left ventricle due to amyloid infiltration, leading to increased size, reduced ejection force, and strain. While LA dimension or volume can suggest chronic elevation of LA pressure, they are insufficient parameters to obtain detailed information about LA function [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…LA strain was measured using specific software (2D Cardiac Performance Analysis; Tomtec Arena 2.42) and end diastole as the zero-strain reference point. 9 LA reservoir function was assessed by the reservoir strain (LASr) and additionally estimated from the product LASr (as a surrogate of LA pressure change [10][11][12] )×LA reservoir volume [13][14][15] -a simplified index of LA reservoir work (LAWr).…”
Section: La Size and Functionmentioning
confidence: 99%